Design and analysis of independent 3-link rear suspension for All-Terrain vehicle. Issue 1 (1st April 2022) - Patel, Pavan; Shah, Vyom; Keshav, Manjeet
Abstract: The fundamental thought behind the paper is to configure, dissect just as recreate the Independent 3-Link suspension math introduced in the back of an Off-road Vehicle (ATV). An ATV as the name recommends is intended to handle a tremendous assortment of landscape than different vehicles. The Suspension framework which is the main imperative for taking care of has gone through a generous measure of advancement previously. Accordingly, the point is centred around planning the previously mentioned suspension framework joining elements of the vehicle with giving ideal execution of the vehicle while expanding driver comfort. Boundaries like camber, wheel travel, roll focus were assessed to achieve the wanted execution. As the ATV's for the most part go through a colossal measure of shocks in harsh landscapes, the soundness of the vehicle was additionally given significance. by arms in CAD software.